REFORMULATION OF THE CRIMINAL LIABILITY AS AN ACTOR OF ONLINE PROSTITUTION: A NORMATIVE STUDY - Juita, Subaidah Ratna (Universitas Negeri Semarang (UNNES), 2017)
One of the rational efforts used to tackle online prostitution activity is with the approach of criminal law through criminal law formulation as a concrete form of criminal responsibility to the perpetrators of online prostitution. There is no provision that regulates the criminal to the users of online prostitution services because of the maximum prevention of online prostitution itself. If there is no national regulation governing the matter, online prostitution users will feel secure and remain free to buy services for their satisfaction alone, while it is contrary to various aspects of norms in the ethical norms of society. Therefore a criminal law is required, related to criminal liability for users of online prostitution services. The method used is normative juridical, ie by examining or analyzing secondary data using basic materials, with legal sense as a set of rules or positive norms in the legislation system that regulates prostitution online, as well as using secondary legal materials, and tertiary. So this research is library research (library research), that is research to secondary data. Thus, the juridical-normative approach in the study is used to analyze issues relating to criminal law reform regarding criminal liability to online prostitution actor.